2020
DOI: 10.1371/journal.pntd.0008570
|View full text |Cite
|
Sign up to set email alerts
|

Air and surface contamination in non-health care settings among 641 environmental specimens of 39 COVID-19 cases

Abstract: Little is known about the SARS-CoV-2 contamination of environmental surfaces and air in non-health care settings among COVID-19 cases. We explored the SARS-CoV-2 contamination of environmental surfaces and air by collecting air and swabbing environmental surfaces among 39 COVID-19 cases in Guangzhou, China. The specimens were tested on RT-PCR. The information collected for COVID-19 cases included basic demographic, clinical severity, symptoms at onset, radiological testing, laboratory testing and hospital admi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…SARS-CoV-2 transmission occurs primarily through respiratory routes, but transmission from contaminated surfaces, or fomites, has been a concern. SARS-CoV-2 RNA has been detected on surfaces in healthcare [1][2][3][4][5][6][7][8] and community [9,10] settings, residences [11], quarantine rooms [3,12], and a cruise ship [13]; however, attempts to culture virus from environmental samples testing positive for SARS-CoV-2 have not been successful [2,3,6,7,13]. Only studies examining the stability of SARS-CoV-2 on surfaces in controlled laboratory settings have found that viable virus can be recovered from plastic and stainless steel for 3-4 days [14,15] and in one study up to 28 days [16], while persistence on porous surfaces, including cardboard and cotton, is shorter [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…SARS-CoV-2 transmission occurs primarily through respiratory routes, but transmission from contaminated surfaces, or fomites, has been a concern. SARS-CoV-2 RNA has been detected on surfaces in healthcare [1][2][3][4][5][6][7][8] and community [9,10] settings, residences [11], quarantine rooms [3,12], and a cruise ship [13]; however, attempts to culture virus from environmental samples testing positive for SARS-CoV-2 have not been successful [2,3,6,7,13]. Only studies examining the stability of SARS-CoV-2 on surfaces in controlled laboratory settings have found that viable virus can be recovered from plastic and stainless steel for 3-4 days [14,15] and in one study up to 28 days [16], while persistence on porous surfaces, including cardboard and cotton, is shorter [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, surface contamination in non-healthcare settings is still poorly studied. In fact, to date, community environments have been studied with reference to episodes of infection, while as far as we know no recreational facilities have been targeted for investigation, especially after sanitation [ 15 ]. These premises lead us to reflect about investigating community environments frequented by many people.…”
Section: Introductionmentioning
confidence: 99%
“…All facilities of all sizes should initiate, on a regularly scheduled basis, air exchange where a high percentage of air within an enclosed environment is exhausted to the outside with the replacement of fresh air. Most facilities currently recirculate their ventilated air, which can contribute to the distribution/spread of the SARS-CoV-2 particle throughout the facility [ 13 , 14 ]. With traditional shared building air exchange systems (ventilation), one infected person in a facility can within minutes contaminate the entire facility [ 15 ].…”
Section: Resultsmentioning
confidence: 99%